Perspectives of SME Financing Through Capital Markets: the Case of Croatia - Jakov Kovač; Frane Šesnić; Jakša Krišto (6th International OFEL Conference on Governance, Management and Entrepreneurship. New Business Models and Institutional Entrepreneurs: Leading Disruptive Change. April 13th - 14th, 2018, Dubrovnik, Croatia, 2018)
Startup companies are very vulnerable and risky part of SME sector, as well as the entire economy. Early stage in company's life cycle, inadequate income and risky market surroundings disenables these companies from accessing sources of financing within traditional financial institutions. Their sources of financing are usually own funds, family, non-refundable support funds and in developed countries business angels and different forms of venture capital. Recognizing insufficient financial support for startups and SME in general, the EU has started an initiative enabling access to equity financing for these companies. The initiative has been regulatory implemented through European venture capital funds (EuVECA), a specific type of alternative investment fund in the EU. The paper points to expected effects of setting up such funds, their regulatory requirements and their market potential in the EU. The aims of a paper are to discuss and examine EuVECA fu nds as a possible instrument for equity financing in Croatia. Paper uses quantitative empirical research using survey methodology on the sample of start-ups in Croatia examining the potential of these companies for equity financing. The paper is also analysing the entire surrounding of equity financing of startups in Croatia from venture capital, support measures of developing agencies and the government as well as EU funds. Based on empirical research and analysis of available instruments of equity financing, the development potential of European venture capital funds (EuVECA) in Croatia is estimated. Special emphasis is given to stimulating framework, access to financial funds and startup companies in urban agglomeration of the City of Zagreb.
Keywords: 650; Startup companies; Equity financing; Venture capital; EuVECA; Croatia